Aerodynamic performance of aerofoils obtained from a geometric offset applied to a given initial aerofoil - Sousa Diogo; Gamboa Pedro; Melo David (Open Engineering, 2016)
Many studies concerning morphing aircraft concepts in which enhanced performance and increased energy efficiency are two of the main goals have been recently conducted. Some of those concepts deal with wing span changes. In line with those, in a variable-span wing of the telescopic type, the cross-sections of the sliding panels, whether be two, three or more, must be made geometrically compatible among them. This requirement serves two purposes: to minimize the aerofoils’ geometric discontinuity which negatively affects wing drag and lift; and to provide a simple structural support between any two sliding panels. This paper describes the methodology employed to develop geometrically compatible aerofoils obtained from a constant geometric offset applied to a given initial aerofoil. This methodology is used to create inward offset aerofoils and outward offset aerofoils. The geometric and aerodynamic characteristics of the resulting offset aerofoils are compared with those of the original aerofoils. From the analysis of six different original aerofoils, strong trends in the geometric changes and in the aerodynamic characteristics of the resulting inward and outward offset aerofoils are observed. Ultimately, this study can help a telescopic wing designer decide whether an inward or an outward offset aerofoil is more appropriate for the specific design at hand.